Insights into the potential application of magnetic field in controlling sludge bulking and foaming: A review. (August 2022) - Syamimi Zaidi, Nur; Syafiuddin, Achmad; Sillanpää, Mika; Burhanuddin Bahrodin, Muhammad; Zhang Zhan, Loh; Ratnasari, Anisa; Kadier, Abudukeremu; Aamer Mehmood, Muhammad; Boopathy, Raj
Graphical abstract: Highlights: Magnetic field application in controlling sludge bulking and foaming is reviewed. Factors affecting sludge bulking and foaming are discussed. Existing approaches are capable but with certain limitations. Understanding the complex process of sludge bulking and foaming is still needed. Abstract: The formation of bulking and foaming in biological wastewater treatment could cause a series of operational issues with biomass and effluent quality, ultimately affect the treatment performance of the system. The essential parameters influencing the growth of bulking and foaming bacteria are comprehensively summarised in this paper. Existing bulking and foaming control approached are critically reviewed and addressed, as well as their drawbacks and limitations. Despite the abundance of information and implementation, a complete control technique for limiting filamentous sludge bulking and foaming remains insufficient. Magnetic field application is emphasised as a viable control strategy in this regard. The present review study provides new insight of this application by comparing the use of magnetic fields to conventional treatments. Future outlooks on the use of magnetic fields to prevent BFB proliferation were also highlighted.